2019
DOI: 10.1007/s13300-019-0602-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antihyperglycemic Drug Use is Associated with Undernutrition Among Older Adults with Type 2 Diabetes Mellitus: A Cross-Sectional Study

Abstract: Introduction Undernutrition is prevalent in older age. Current management of type 2 diabetes mellitus (T2DM) requires modified diet patterns; however, older adults with diabetes may also be at the risk of undernutrition due to age, disease, and medication-related factors. Our objectives in this study were to examine the proportion and associations of undernutrition among community-dwelling older adults with T2DM. Methods This prospective, cross-sectional study involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
3
2
Order By: Relevance
“…However, functional ability (both basic and instrumental ADL) was correlated with MNA scores ( 65 ) . However, unlike previous research ( 51 , 66 ) , no association was found between these factors and poor nutrition in the current study. This disparity could be due to differences in the measures and tools used to assess functional capacity between this and previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, functional ability (both basic and instrumental ADL) was correlated with MNA scores ( 65 ) . However, unlike previous research ( 51 , 66 ) , no association was found between these factors and poor nutrition in the current study. This disparity could be due to differences in the measures and tools used to assess functional capacity between this and previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Vischer et al ( 19 ) reported a positive association between MNA scores and HbA1c levels but focused on older patients with T2DM admitted to a geriatric hospital, unlike our outpatient clinic cohort. Junaid et al ( 9 ) and Tasci et al ( 51 ) showed that older adults with poorly controlled diabetes had an increased risk of poor nutritional status (50–88 %), whereas the present study found a lower prevalence of poor nutrition (15·0 %) and malnutrition (0·03 %). The main difference lies in the criteria for categorising patients into the adequate alchemically controlled group.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In a study including 2329 geriatric patients hospitalized in Belgium, malnutrition was detected in 31% of the diabetic patients 17 . Although nutritional evaluation studies conducted with outpatients are rarely cited in the literature, in a study conducted by İlker Taşci et al 7 in our country, undernutrition was more common among older patients with type 2 diabetes. NRS scores of our patients with lower education levels were higher than those with higher education levels.…”
Section: Discussionmentioning
confidence: 74%
“…In a study conducted at Istanbul University, malnutrition risk was 31% and malnutrition rate was 13% in patients who were admitted to the outpatient clinic, whereas malnutrition risk was determined as 39% and malnutrition rate as 25% in hospitalized patients 5 , 6 . In another study, it was found that malnutrition is a common nutritional problem in older outpatient adults 7 . In a study conducted in Turkey, it was reported that the prevalence of malnutrition increases especially with age, making management of diabetes difficult 8 .…”
Section: Introductionmentioning
confidence: 98%